Comparison of three cooling methods for burn patients: A randomized clinical trial. Issue 3 (May 2017) - Cho, Young Soon; Choi, Young Hwan
Highlights: Cooling with tap water is a well-known initial first aid in burn patients. Tap water and Burn Cool spray ® reduced the skin surface temperature but Burnshield ® increased it. Tap water, Burn Cool spray ® and Burnshield ® were effective for relieving pain. The temperature of tap water was related to the effect of cooling. The patients who visited within 30 min of the burn accident needed cooling for more than 20 min. Abstract: Tap water may not be readily available in numerous places as a first aid for burns and, therefore, tea tree oil products are recommended alternatives. Our aim in this study was to compare the cooling effects of three burn-cooling methodologies, running tap water, Burnshield ®, and Burn Cool Spray ®, and suggest indications for each cooling method. This randomized, controlled, study enrolled patients with burns who used the emergency service of Seoul Bestian Hospital from June 2015 to October 2015. The allocation of the cooling methods was randomly generated using a computer. We cooled the burn wounds by applying one of the three methods and measured the skin surface temperature and pain level using a visual analog scale (VAS) scoring. Ninety-six patients were enrolled in this study. The variability in the median(IQR) skin temperatures of the three groups was from 33.5 °C (31.5–35.0) to 28.7 °C (25.9–30.9), 33.8 °C (32.0–35.4) to 33.2 °C (30.5–35.0), and 34.0 °C (32.0–35.1) to 34.4 °C (32.7–35.6) for the tap water, Burn Cool Spray ®, and Burnshield ®, respectively. The variability of the mean VAS pain scores was 6.9 to 4.8 (tap water), 5.6 to 4.5 (Burn Cool Spray ® ), and 5.5 to 3.3 (Burnshield ® ). The reduction of skin surface temperature by tap water was significantly greater than that by the other two methods. All three methods reduced the VAS pain score after 20 min of treatment ( p < 0.001). The tap water had a similar effect to that of the Burn Cool Spray ® but significantly better than that of Burnshield ® . There was a significant difference in the skin surface temperature and VAS pain score reduction ( p = 0.014 and p = 0.007, respectively) between the groups cooled by tap water below and above 24 °C. The patients who visited the center within 30 min showed a significantly higher skin temperature than those who came after 30 min did ( p = 0.033). Tap water and Burn Cool Spray ® reduced the skin surface temperature, but the Burnshield ® slightly increased it. All three cooling methods were effective in relieving pain. The temperature of the tap water used was related to the reduction in skin surface temperature and VAS pain score. The patients who visited the hospital within 30 min of their burn accident needed a longer cooling time to attain a comparable skin surface temperature to those who visited after 30 min.